Fundamental experiments of radio‐frequency preionized inert gas plasma MHD electrical power generation. Issue 4 (10th July 2019) - Nakane, Takayuki; Uehigashi, Katsuya; Iwamoto, Takuya; Okuno, Yoshihiro
Abstract: A seed‐free radio‐frequency (RF) preionized inert gas plasma MHD electrical power generation has been first demonstrated in fundamental experiments with a shock‐tunnel facility. An enthalpy extraction ratio of 2.6% was successfully obtained even under an inlet total temperature of 2200 K at which the power generation can be operated continuously. Since the RF input power required for the preionization tends to be increased for lower inlet total temperature, the reduction of the RF input power is needed for further improvement in the total performance.